KAFAâAH IN ISLAM: Towards a Pogressive Interpretation - Nur, Iffatin (EpistemÃƒÂ©: Jurnal Pengembangan Ilmu Keislaman, 2014)
Etimologically, the word kafaâah means egalitarian, equivalent, comparable, orsimilar. In the constellation of the Islamic thought, kafaâah is meant that a prospective husband is expected to be comparable to the prospective bride in terms of religion, education, social status, profession, descent/ancestry, independence status, physical-spiritual conditions, wealth, position, degree and so on. It is intended to guarantee the relation between a husband and his wife as well as ensuring a harmony oftheir family life in the future. This article describe about kind of Moslemâs thinker perspective, especially about kafaâah concept. Some of the recommend a strict implementation of kafaâah from the point of religion to the factor of wealth that the prospective groom must meet all the detailed requirements; but some others do not give much regards to it. The latter grounds their views on a reason that any Moslem, as long as he is not an adulterer, has the right to marry any Moslemâs woman he want. Kafaâah secara etimologi berarti egaliter; sepadan; sebanding; semisal. Dalam konstalasi pemikiran Islam, kafaâah dimaksudkan bahwa seorang calon suami diharapkan sebanding dengan calon istri dalam agama, tingkat pendidikan, status sosial, profesi, keturunan, kemerdekaan, kondisi jasmani-rohani, kekayaan, jabatan, derajat dsb. Hal ini dimaksudkan agar terjaminnya keharmonisan pergaulan suami istri dalam berumah tangga di kemudian hari. Artikel ini coba menguraikan beragam pandangan para pemikir Muslim mengenai konsep kafaâah. Ada yang mensyaratkan secara ketat pelaksanaan kafaâah, sejak poin agama sampai poin kekayaan; di mana kriteria calon mempelai laki-laki harus memenuhi secara terinci persyaratan di atas. Namun ada juga yang sama sekali tidak melihat kepentingan kafaâah ini, dengan alasan Muslim mana saja, asal tidak pezina, memiliki hak untuk menikahi Muslimah yang diinginkannya.